Tinjauan Kurikulum Merdeka Belajar dengan Model Pendidikan Abad 21 dalam Menghadapi Era Society 5.0 - Hasanah, Arinal; Haryadi, Haryadi (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2022)
Society 5.0 is a is a society that can solve various cases using technological developments that were born from the industrial revolution 4.0. This period can be an opportunity and a challenge, especially in the world of education. Education must be able to answer challenges and at the same time must also improve in order to meet the needs of the community. The independent curriculum is one of the efforts to realize student-oriented education (student center), and the 21st century education model is present as a role model of ideal education in this modern era. This research is a library research with descriptive data description model. The focus of this research is the correlation between the independent learning curriculum and the 21st century learning model in facing the era of society 5.0. The correlation between the independent learning curriculum and the 21st century learning model cannot be separated. The position of the 21st century education concept as a general framework that becomes a reference for education, while the independent learning curriculum is a technical or method implemented to achieve this general framework. The independent curriculum and the 21st century education model were born as a form of response to the challenges posed by the industrial revolution era 4.0 and the era of society 5.0. The independent curriculum and the 21st century education model are interrelated and interrelated.